Job search mobility and remittance: The case of corner village in Kediri Regency, East Java - Irdaf Irdaf (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Even though the population growth in East Java at SUPAS 2015 has decreased (1.9% per year) but it has the consequence of increasing the number of workforce along with the agricultural land is getting narrower and the carrying capacity of the environment decreases. Along with that, non-agricultural employment opportunities in rural areas are increasingly scarce, this condition encourages residents to leave their home areas and seek livelihoods in other areas. There are two reasons why the international mobility workforce because employment opportunities in the country are not comparable to the number of job seekers. Both employment opportunities of relatively rich and developing countries can absorb large numbers of Indonesian labor migrants. Especially the Middle East, Malaysia, Singapore and other Asean countries. In addition, the country can provide attractive income so that it can improve the standard of living of workers and foreign exchange. Migrant workers who have worked in destination countries can streamline the migration of migrant workers. Besides that there has been dependence between Indonesian and Malaysian workers. In development in Malaysia, many workers in the country have middle to upper education who are reluctant to work on plantations and construction. On the other hand in Indonesia the excess of job seekers and wages is relatively very low. Although the employment status of migrant workers can be said to be low, their income is relatively large and can be sent to areas of origin as remittances for living and education costs. But for future thinking, some think about developing a livestock business, poultry shop, RPA. These livestock activities can reduce unemployment in rural areas and can create productive businesses so that they do not depend on the families of migrant workers and can gather with household members and reduce social problems given that this village has an informal informal sector (prostitution).